1995
DOI: 10.1530/eje.0.1320181
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoconjugated and free plasma catecholamine levels at rest and during exercise in patients with idiopathic dilated cardiomyopathy

Abstract: Plasma levels of sulfoconjugated (sc) catecholamines (CA) have been shown to be increased with activation of the sympathoadrenal system in a number of clinical settings. We evaluated the relation between scCA and clinical or hemodynamic parameters of patients with idiopathic dilated cardiomyopathy (IDC) at rest and during incremental exercise testing. Eleven healthy subjects, nine patients in New York Heart Association (NYHA) functional class I (IDC-A group) and 11 in NYHA functional class II and III (IDC-B gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…9,[18][19][20] Although the precise regulatory mechanisms for the activity of these enzymes remain unclear, the deconjugation of conjugated dopamine to free dopamine is known to increase in patients with chronic heart failure, 21 in whom sympathetic activation occurs chronically. This finding is compatible with previous reports 9,22 showing that plasma free dopamine levels are increased by sympathetic nervous activation. The circulating concentration of conjugated dopamine is the highest among the concentrations of the circulating catecholamines, usually 5-to 10-fold higher than all others, conjugated or free norepinephrine and epinephrine.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…9,[18][19][20] Although the precise regulatory mechanisms for the activity of these enzymes remain unclear, the deconjugation of conjugated dopamine to free dopamine is known to increase in patients with chronic heart failure, 21 in whom sympathetic activation occurs chronically. This finding is compatible with previous reports 9,22 showing that plasma free dopamine levels are increased by sympathetic nervous activation. The circulating concentration of conjugated dopamine is the highest among the concentrations of the circulating catecholamines, usually 5-to 10-fold higher than all others, conjugated or free norepinephrine and epinephrine.…”
Section: Discussionsupporting
confidence: 94%
“…The circulating concentration of conjugated dopamine is the highest among the concentrations of the circulating catecholamines, usually 5-to 10-fold higher than all others, conjugated or free norepinephrine and epinephrine. 21,22 Therefore, free dopamine levels are greatly influenced by the deconjugation of conjugated dopamine, and this conjugation is also stimulated by cortisol, 23 which is released in the condition of heart failure. Furthermore, the transient increase in free dopamine levels after physiological stress is less as compared with norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced rate of NE increase during exercise in patients with HF in comparison to controls was first described by Francis [4]. Similar results were reported by Dobnig et al [5]. Conversely, other authors observed a more marked increase in plasma NE during exercise in patients with HF compared to normal subjects [6, 7].…”
Section: Introductionsupporting
confidence: 84%
“…85 In patients with idiopathic dilated cardiomyopathy exposed to exercise, plasma DA sulfate proved to be an even better marker of sympathetic discharge than free NA. 86 DA receptors were found not only in the kidney but also in the heart 87 and to be involved in heart failure. Increased DA is probably balanced by DA receptor downregulation in the failing heart protecting it against further DA stimulation.…”
Section: Dopamine In Secondary Hypertension and Associated Conditionsmentioning
confidence: 99%